Acceptance and reverification testing for industrial computed tomography - a simulative study on geometrical misalignments - Wohlgemuth, Florian; Hausotte, Tino; Schmidt, Ingomar; Kimmig, Wolfgang; Imkamp, Karl Dietrich (Journal of Sensors and Sensor Systems, 2022)
Acceptance and reverification testing for industrial X-ray computed tomography (CT) is described in different standards (E DIN EN ISO 10360-11:2021-)4, 2021; VDI/VDE 2630 Blatt 1.3, 2011; ASME B89.4.232020, 2020). The characterisation and testing of CT system performance are often achieved with test artefacts containing spheres. This simulative study characterises the influence of different geometrical error sources - or geometrical misalignments - on these sphere measurements. The two measurands on which this study focuses are the sphere centre-to-centre distances and the sphere probing form errors.
CRIS-Team WoS Importer:2022-07-01

Automated evaluation of the surface point quality in dimensional X-ray computed tomography - Müller, Andreas; Butzhammer, Lorenz; Wohlgemuth, Florian; Hausotte, Tino (Technisches Messen, 2020)
X-ray computed tomography (CT) enables dimensional measurements of numerous measurands with a single scan, including the measurement of inner structures. However, measurement artefacts complicate the applicability of the technology in some cases. This paper presents a methodology to assess the surface point quality of computed tomography measurements without the requirement of a CAD model. Measurement artefacts lowering the surface point quality can therefore automatically be detected. The correlation of quality values with the random measurement error is demonstrated. The presented method can in principle be used to weight single fit points to reduce the measurement uncertainty of CT measurement
Keywords: Industrial X-ray computed tomography; surface point quality; volume data; segmentation

Convergence Behaviour of Numerical Measurement Uncertainty Evaluation using a Virtual Metrological Computed Tomography System - Wohlgemuth, Florian; Hausotte, Tino (10th Conference on Industrial Computed Tomography (iCT 2020), 2020)
Keywords: numerical measurement uncertainty evaluation; convergence; digital twin; dimensional metrology

Determination of Metrological Structural Resolution using an Aperiodic Spatial Frequency Standard - Wohlgemuth, Florian; Fleßner, Matthias; Hausotte, Tino (International Symposium on Digital Industrial Radiology and Computed Tomography – DIR2019, 2019)

Development of a virtual metrological CT for numerical measurement uncertainty determination using aRTist 2 - Wohlgemuth, Florian; Müller, Andreas; Hausotte, Tino (Technisches Messen, 2018)
The development of a virtual metrological CT for numerical measurement uncertainty determination at the Institute of Manufacturing Metrology (FriedrichAlexander- University Erlangen-Nuremberg (FAU), Germany) using the software aRTist 2 by the BAM German Federal Institute for Materials Research and Testing is described. The virtual metrological CT uses a Monte-Carlo approach for numerical measurement uncertainty determination. Results demonstrating that numerical uncertainty determination according to GUM Supplement 1 and in accordance with uncertainty determination according to guideline VDI/VDE 2630 Part 2.1 is possible for selected measurement tasks are presented.
Keywords: X-ray computed tomography; Monte Carlo simulation; aRTist 2; metrology; measurement uncertainty

Digitale Zwillinge metrologischer Röntgencomputertomografen für die numerische Messunsicherheitsbestimmung - Wohlgemuth, Florian; Wolter, Frederike; Hausotte, Tino (ZfP heute. Wissenschaftliche Beiträge zur zerstörungsfreien Prüfung 2020, 2020)

Ein praxisnaher Leitfaden für computertomografische Untersuchungen mit der radiografischen Simulationsumgebung aRTist - Binder, Felix; Bellon, Carsten; Wohlgemuth, Florian; Hausotte, Tino (DGZfP-Jahrestagung 2021, 2021)
Radiografische Simulationswerkzeuge wie aRTist, ScorpiusXLab, SimCT oder CIVA CT verwenden analytische Methoden und physikalische Monte-Carlo-Teilchentransportsimulationen, um die Interaktionsprozesse zwischen Röntgenstrahlung und Materie zu simulieren. Die berechneten Projektionen bilden anschließend unter Berücksichtigung einer definierten Scan-Trajektorie die Basis der Simulation einer röntgencomputertomografischen Untersuchung. Für den erfolgreichen Einsatz der Computertomografie, sei es als zerstörungsfreie Prüfmethode oder beim dimensionellen Messen, ist es generell notwendig, bekannte Fehler- bzw. Abweichungsquellen des Messverfahrens auszuschließen oder zu reduzieren. Dabei hat sich gezeigt, dass die Auswahl der Messparameter und die Erfahrung des Anwenders direkten Einfluss auf das erzielbare Messergebnis einer computertomografischen Untersuchung nehmen. Es ist daher sinnvoll, die Parameterauswahl in einem virtuellen Simulationsaufbau vorher zu erproben und an die Messaufgabe anzupassen. Neben der Optimierung von Messparametern finden radiografische Simulationswerkzeuge auch Anwendung für Machbarkeitsstudien und werden zur Schulung von Anwendern im Bereich der Röntgen-Computertomografie verwendet. Radiografische Simulationswerkzeuge befinden sich in einem stetigen Wandel, beispielsweise durch die Entwicklung neuer Rekonstruktionsmethoden, durch Erweiterung von analytischen Modellen, durch Integration komplexer Trajektorien oder durch Berücksichtigung von prozessbedingten geometrischen Abweichungen. Im laufenden EMPIR-Projekt „AdvanCT“ entsteht deshalb ein „Good Practice Guide“ für die Simulationsumgebung aRTist. Ziel dieses Guides ist es, die mit steigender Komplexität verbundenen Einstiegshürden für Anwender von aRTist zu reduzieren, um damit einen praxisnahen Zugang zur virtuellen Computertomografie zu ermöglichen. Dabei werden anhand von praktisch nachvollziehbaren Beispielen die grundlegenden Mechanismen der Simulationsumgebung erklärt und ein strukturierter Leitfaden zur Simulation röntgencomputertomografischer Untersuchungen mit aRTist vermittelt. In diesem Beitrag werden erste Auszüge des Guides sowie eine Übersicht der weiteren geplanten Themen für die anschließende Diskussion vorgestellt.<br
Keywords: Computertomografie; aRTist; Simulation

Influence of Continuous Scan Mode and Workpiece Positioning on Dimensional Measurements with Computed Tomography - Orgeldinger, Christian; Wohlgemuth, Florian; Hausotte, Tino (SMSI 2021 - Measurement Science, 2021)
The determination of measurement uncertainties in dimensional X-ray computed tomography measurement technology is a complex task for which many different influences have to be taken into account. This work examines the influence of the scan mode in combination with the number of projections and an eccentric clamping on the quality of the measurement. It shows that the workpiece positioning has a considerable influence on the result in the case of continuous scan mode. In addition, an applicationdependent potential for reducing the lead times is described.<br
Keywords: X-ray computed tomography; measurement uncertainty; scan mode; workpiece position-ing; dimensional metrology

Measurement-based Detector Characteristics for Digital Twins in aRTist - Reuter, Tamara; Wohlgemuth, Florian; Bellon, Carsten; Hausotte, Tino (20th World Conference on Non-Destructive Testing, 2024)

Modelling of Pore Collapse during Polymer Sintering: Viscoelastic Model with Enclosed Gas - Wohlgemuth, Florian; Lellinger, Dirk; Alig, Ingo (Materials, 2021)
Frenkel’s model for the late stage of coalescence of viscous particles has been extended to describe pore collapse in a viscoelastic melt during polymer sintering. The shrinkage of a pore in a polymer melt driven by surface tension is extended by taking into account the effects of trapped gas and gas transport out of the pore. Viscoelasticity has been shown to have a considerable impact on the time scale of the coalescence process. In addition, gas diffusion modifies the coalescence dynamics. Based on a parameter study, different regimes for the pore collapse have been identified. At the beginning of pore collapse, surface tension is considerably stronger than gas pressure within the pore. In this time interval (surface-tension-driven regime), the pore shrinks even in the absence of gas diffusion through the matrix. In the absence of gas transport, the shrinkage dynamic slows down and stops when the surface tension balances the gas pressure in the pore. If gas transport out of the pore is possible, surface tension and gas pressure are balanced while the gas pressure slowly decreases (diffusion-controlled regime). The final phase of pore collapse, which occurs when the gas pressure within the pore decreases sufficiently, is controlled again by surface tension. The limitations of the model are discussed. To analyze the interplay between different mechanisms and process steps during selective laser sintering, the respective time scales are compared using experimental data.<br
Keywords: polymer sintering; pore collapse; coalescence dynamics; viscoelastic flow; surface tension; gas transport

Numerical determination of task-specific measurement uncertainty using a virtual metrological X-ray computed tomography system - Wohlgemuth, Florian; Haltenberger, Eric; Klein, Christopher; Hausotte, Tino (Sensoren und Messsysteme, 2018)

Numerische Bestimmung der aufgabenspezifischen Messunsicherheit mit Hilfe eines virtuellen metrologischen Röntgencomputertomografen - Helmecke, Eric; Wohlgemuth, Florian; Klein, Christopher; Hausotte, Tino (2017)

Realistic Simulation of Specific CT-Systems in aRTist 2 - Wohlgemuth, Florian; Hausotte, Tino (DGZfP-Jahrestagung 2021, 2021)

Road to uncertainty – how virtual CT models could evaluate task specific measurement uncertainties - Binder, Felix; Wohlgemuth, Florian; Hausotte, Tino (EUSPEN Virtual International Conference - Workshop: Uncertainty in dimensional X-ray computed tomography, 2020)
Computed tomography (CT) is regularly used in industrial applications for non-destructive testing. Due to the complexity of the measurement process, analytical approaches to evaluate task specific uncertainties are currently infeasible. Available methods as described in the VDI/VDE standard 2630 Part 2.1 do not meet the criteria of scalability and cost efficiency. Therefore alternatives, like the Monte Carlo based approach described in the GUM Supplement 1, are promising to evaluate task specific uncertainties even on an industrial scale. The talk will present a basic framework for this approach and provide an inside view of the current research in this field. <
Keywords: Computed Tomography; Task Specific Measurement Uncertainty; Virtual CT

Simulation-based correction of systematic errors for CT measurements - Müller, Andreas; Wohlgemuth, Florian; Hausotte, Tino (8th Conference on Industrial Computed Tomography, 2018)
A large number of influencing quantities can induce measurement deviations for dimensional measurements using computed tomography. The article describes a newly developed simulation-based correction method for computed tomography coordinate measurements. Using a steel gauge block it is demonstrated that the method can significantly reduce the deviation of the measured surface from the real form of the measurement object. The computed tomography system used has a maximum acceleration voltage of 130 kV. Therefore, a steel gauge block is a relatively challenging measurement object due to the likely occurrence of beam hardening artefacts. The results show that, for a given computed tomography system, the described method can extend the range of objects for which dimensional measurements are feasibl
Keywords: X-ray computed tomography; simulation; artefacts; correction; systematic error; ray tracing

Spot size and detector unsharpness determination for numerical measurement uncertainty determination - Orgeldinger, Christian; Wohlgemuth, Florian; Müller, Andreas; Hausotte, Tino (9th Conference on Industrial Computed Tomography, 2019)
As the experimental measurement uncertainty evaluation for comp uted tomography is currently an expensive and time-consuming task, numerical uncertainty evaluation (according to GUM Supplement 1) using a virtual CT is a promising alternative. For this digital twin to simulate accurate measure ment results, the virtual CT system needs to be modelled as reallistically as possible using adequate input parameters for the simulation. This paper describes a method for the separateddetermination of two significant input parameters: focal spot size and detector unsharpness. The method is tested using a widerange of measurement parameters on a Zeiss Metrotom 1500 with different test specimen. It could be shown that the method yields reasonable results for most parameters. In addition, the re is a dependence of the focal spot size on the ratio of tube voltage and tube current at constant power. This contradicts the wide-spread rule of thumb that the spot size depends on the tube power only. Indications of a changing focal spot shape at high powers could be detecte
Keywords: ocal spot; detector unsharpness; numerical measurement uncertainty evaluation; virtual coordinate measuring machine; dimensional metrology

The CTSimU software toolbox for CT-related image processing and quality assessment - Plotzki, David; Hartlaub, Bendix; Borges de Oliveira, Fabrício; Reuter, Tamara; Wohlgemuth, Florian; Bellon, Carsten; Hausotte, Tino (11th Conference on Industrial Computed Tomography (iCT) 2022, 8-11 Feb, Wels, Austria (iCT 2022), 2022)
A software toolbox is introduced that addresses several needs common to computed tomography (CT). Built for the WIPANO CTSimU project [1] to serve as the reference implementation for its image processing and evaluation tasks, it provides a Python 3 interface that is adaptable to many conceivable applications. Foremost, the toolbox features a pipeline architecture for sequential 2D image processing tasks, such as flat field corrections and image binning, and enables the user to create their own processing modules. Beyond that, it provides means to measure line profiles and image quality assessment algorithms to calculate modulation transfer functions (MTF) or to determine the interpolated basic spatial resolution (iSRb) using a duplex wire image [2]. It can also be used to calculate projection matrices for the reconstruction of scans with arbitrary industrial CT geometries and trajectories. The CTSimU project defined a framework of projection- and volume-based test scenarios [3] for the qualification of radiographic simulation software towards its use in dimensional metrology. The toolbox implements the necessary evaluation routines and generates reports for all projection-based tests. <br

Towards efficient application-dependent dimensional measurements with computed tomography: optimized reduction of measurement duration using continuous scan mode: experimental investigations - Orgeldinger, Christian; Wohlgemuth, Florian; Müller, Andreas; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2022)
Due to the complex physical and technical relationships in dimensional X-ray computed tomography measurement technology, the precise influences on the measurement result are still not fully understood. A deeper understanding of these influences is essential in order to improve the measurement accuracy and economy of computed tomographic measurement systems. In addition, this enables better numerical determination of measurement uncertainties, which is also a topic of current research. Two factors that have a significant influence on the lead times are the scan mode and the number of projections per measurement. In this article, these factors are investigated experimentally using a calibrated workpiece, and the influence of the workpiece position on the measurement result is also examined. It can be shown that the workpiece position has a considerable influence on the quality of the measurement, especially in the case of a continuous scan. The results show a vast potential for application-dependent reduction of lead time

Virtuelle dimensionelle Röntgencomputertomografie für die numerische Messunsicherheitsbestimmung - Reuter, Tamara; Wohlgemuth, Florian; Hausotte, Tino (10. VDI-Fachtagung Messunsicherheit und Prüfprozesse 2021, 2021)